Assessment of knowledge, perception, and attitude towards causes related to climate change among the undergraduates of the non-science students of Universiti Teknologi MARA, Perlis branch / Sharir Aizat Kamaruddin ... [et al.] - Kamaruddin, Sharir Aizat; Adnan, Fazrul Redha; Anuar, Muhammad Hasif; Saiffullah Asrif, Izyan; Zulkefle, Muhammad Muhaimin; Aiman Azaha, Muhamad Nasiruddin; Ahmad, Muhammad Nasrul; Arshad, Munawwarah (Universiti Teknologi MARA, Perlis, 2022)
The purpose of this study is to assess the respondents' knowledge and attitudes towards causes related to climate change and their behaviour towards climate change. An online questionnaire has been distributed to non-science students at the Universiti Teknologi MARA, Cawangan Perlis, Kampus Arau, Perlis. A total of 42 respondents have responded to the survey. The study assesses the participant's knowledge of climate change, attitude, and individual behaviour to cope with climate change. Most respondents offered positive responses to the questions about climate change knowledge and attitudes, as well as their perceptions of climate change. The study also acknowledges the awareness of climate change that has been raised among non-science students. Additionally, this is to support the appropriate climate change initiatives in conjunction with the proposed policies that promote sustainable development.